White-Box Cryptography Opportunities for Secure Online Assessments - Coelho, Matheus Gomes Martins; Rodrigues, Felix Carvalho (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
Secure online assessments depend on software running on student-controlled devices, which leaves exam clients exposed to reverse engineering, tampering, and code lifting. This creates a natural, but still underexplored, use case for white-box cryptography. Using Safe Exam Browser as a concrete case, we discuss how white-box techniques can strengthen assessment workflows without assuming trusted hardware on every student device. We identify the assets that benefit most from software protection and define a pragmatic attacker model for digital examinations. We outline an initial pragmatic design in which a narrow protected client module supports device and application binding for short-lived operations such as token release and protected content access.